THE INFLUENCE OF SALES GROWTH AND TOTAL ASSETS ON COMPANY PROFITS IN PROPERTY COMPANIES - Morina Lavega Meliala; Seftiaghika Sri Winta Pandia; Arie Pratania Putri (Mount Hope Economic Global Journal, 2024)
A property company is an entity that plays a role in developing, selling, renting, and managing properties such as housing, apartments, and commercial buildings. The property industry in Indonesia has experienced significant dynamics over the last few years, especially seen in the effects of the COVID-19 outbreak, which has impacted the development and stability of this sector. After experiencing a significant decline in 2020, the property sector recovered in 2021 and experienced positive growth. This recovery was triggered by the development of each individual's purchasing power and economic balance after the critical phase. This study is targeted at analyzing the impact of sales growth and total assets on company profits for property companies verified on the IDX from 2021-2023. This study uses a quantitative method using a multiple linear regression approach. This study uses secondary data obtained from the company's annual financial data verified on the IDX; the total sample for this study is 66 samples. The results of the study show that sales growth does not have a significant impact on company profits, and total assets have a significant impact on company profits. Then it shows whether sales growth and total assets have an impact on company profits together. It is hoped that these findings will provide insight for readers.